The synthesis, characterization and photophysical properties of some new cyclotriphosphazene derivatives bearing Schiff base - Aslan, Fatih; Demirpence, Zehra; Tatsiz, Ramazan; Turkmen, Hasan; Ozturk, A. Ihsan; Arslan, Mustafa (Wiley-V C H Verlag Gmbh, 2008)
Hex a(2-formylphenoxy)cyclotriphosphazene (o-CHO-C6H4O)(6)N3P3 (2) was obtained from the reaction of hexachlorocyclotriphosphazene (1) with salicylaldehyde in the presence of K2CO3 in THF solvent. A series of Schiff bases containing cyclo-triphosphazenes such as [o-(C6H5N=CH)C6H4O](6)N3P3 (3), [o-(1-C10H7N=CH)C6H4O](6)N3P3 (4), [o-(p-HOC6H4N=CH)C6H4O](6)N3P3 (5), [o-(2,3-Cl2C6H3N=CH)C(6)H4O](6)N3P3 (6), [o-(3,4-Cl2C6H3N=CH)C6H4O](6)N3P3 (7), [o-(3,5-(CH3)(2)C6H3N= CH)C6H4O](6)N3P3 (8), [o-(C6H5CH2N=CH)C6H4O](6)N3P3 (9), [o-(p-CH3OC6H4CH2N=CH)C6H4O](6)N3P3 (10), [o-(n-CH3CH2CH2CH2N=CH)C6H4O](6)N3P3 (11), [o-(t-(CH3)(3)CN=CH)C6H4O](6)N3P3 (12), [o-(n-CH3[CH2](10)CH2N=CH)C6H4O](6)N3P3 (13) were synthesized from the reaction of hexa(2-formylphenoxy)cyclotriphosphazene (2) with aniline, 1-naphthylamine, 2-amino-phenol, 2,3-dichloroaniline, 3,4-dichloroaniline, 3,5-di-tert-butylaniline, benzylamine, p-methoxybenzylamine, n-butylamine, tertbutylamine and 1-dodecylamine, respectively The synthesized compounds were obtained in good yield and high purity. The structures of the compounds were confirmed by means of IR, NMR(H-1, C-13, P-31) and elemental analysis. Photophysical properties of the cyclotriphosphazene derivates were investigated in dichloromethane solvent by UV-Vis. spectrophotometry and spectrofluorometry (emission and excitation). Among the synthesized cyclotriphosphazene derivates, the compounds 2, 4, 5, 11 and 12 exhibit emission between 390 and 550 nm at room temperature.
Keywords: phosphazene; cyclotriphosphazene; Schiff bases; fluorescence; salicylaldehyde